Regeneration and Training Program for Muhammadiyah Young Preacher Muhammadiyah Regional Head in the City of Malang Indonesia - Haris, Abdul (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to figure out the factors influencing the Regeneration and Training Program for Muhammadiyah Young Preacher conducted by the Preaching Assembly of Muhammadiyah Regional Head in the City of Malang and to identify the training process of the program. This study applies a qualitative method using observation and interviews as the data collection. The data is validated with triangulation and member-check and analyzed using Milles and Huberman interactive techniques. The result shows that the program is influenced by the decreasing concerns of Muhammadiyah competent young preacher amid a social development that demands the higher quality of the preaching services. The process of the program has followed the procedures set by the Muhammadiyah Regional Head, with modification in the implementation and evaluation process. This program gives good benefits to the participants as well as to Muhammadiyah Organisation. The use of moving class of the mosques to the mosques as the training organizer, which involves all the components of Muhammadiyah’s association, as well as integrated evaluation becomes a different feature that can be developed for the program